American Politics in Two Dimensions: Partisan and Ideological Identities versus Anti‐Establishment Orientations. Issue 4 (15th July 2021) - Uscinski, Joseph E.; Enders, Adam M.; Seelig, Michelle I.; Klofstad, Casey A.; Funchion, John R.; Everett, Caleb; Wuchty, Stefan; Premaratne, Kamal; Murthi, Manohar N.
Abstract: Contemporary political ills at the mass behavior level (e.g., outgroup aggression, conspiracy theories) are often attributed to increasing polarization and partisan tribalism. We theorize that many such problems are less the product of left‐right orientations than an orthogonal "anti‐establishment" dimension of opinion dominated by conspiracy, populist, and Manichean orientations. Using two national surveys from 2019 and 2020, we find that this dimension of opinion is correlated with several antisocial psychological traits, the acceptance of political violence, and time spent on extremist social media platforms. It is also related to support for populist candidates, such as Trump and Sanders, and beliefs in misinformation and conspiracy theories. While many inherently view politics as a conflict between left and right, others see it as a battle between "the people" and a corrupt establishment. Our findings demonstrate an urgent need to expand the traditional conceptualization of mass opinion beyond familiar left‐right identities and affective orientations.